Changes in cytokine profile may predict therapeutic efficacy of infliximab in patients with ulcerative colitis. Issue 10 (October 2015) - Sato, Shoko; Chiba, Toshimi; Nakamura, Shotaro; Matsumoto, Takayuki
Abstract Background and Aim Infliximab is an established therapy for ulcerative colitis (UC). The aim of this study was to examine various serum cytokine levels and to identify possible markers predictive of therapeutic efficacy of infliximab for UC patients. Methods Twenty‐one patients with moderately active UC were given intravenous infliximab (5 mg/kg) at 0, 2, and 6 weeks as induction therapy. The serum levels of 17 cytokines were determined using a Bio‐Plex suspension array system before and 8 weeks after induction therapy. Partial Mayo score (PMS) and serum C‐reactive protein levels were used for the determination of clinical activities at 0 and 8 weeks after the treatment. The overall therapeutic effect was determined at 26 weeks according to the PMS. Results The median value of the PMS decreased significantly 8 weeks after the treatment (from 6 to 1.5, P < 0.05). However, C‐reactive protein levels did not change significantly. Levels of serum interleukin (IL)‐8 (P < 0.05) and macrophage inflammatory protein‐1β (P < 0.005) significantly decreased 8 weeks after the induction. Serum levels of the other 15 cytokines did not change significantly. At 26 weeks, 13 of 20 patients (65%) were responders while 7 patients were non‐responders. Levels of serum IL‐6 at 8 weeks were significantly lower in responders than in non‐responders (P < 0.05). Conclusions Serum IL‐8 and macrophage inflammatory protein‐1β seem to be sensitive markers for UC patients treated with infliximab, while IL‐6 at 8 weeks after induction therapy may be predictive of subsequent response to infliximab.